INTEGRATED GEOPHYSICAL EXPLORATION OF A KNOWN GEOTHERMAL RESOURCE: ULU SLIM, HOT SPRINGS, PERAK. - BIN ABDUL RAHIM, ABDUL WHOZAIFAH (Universiti Teknologi PETRONAS, 2015)
Although they are more than sixty hot spring location have been found in the Malaysian Peninsula, the source and origin of the hot springs are still unknown since most of the studies conducted was focused more on the temperature and water quality of the springs. Therefore, this study will discuss the origin of Ulu Slim hotspring using integrated geophysical exploration method. From the previous research, the hotspring area is on or close to granite intrusions and at major fault zones. The recent observation shows that the Ulu Slim hotspring flows towards the surface through small fractures or faults of granite body at the study area. These observations are suggestive for a model that combines the thermal gradient and the cooling magma models. The granitic intrusion represents the cooling magma that can increase the temperature of the rocks in the area. These granites bodies have also become embedded in the earth crust from Late Carboniferous until Late Cretaceous and continuing to disperse heat after solidification as a result of the thermal gradient. The meteoric water flow into the deeper region through pores and permeable rocks. Those waters will hit the rock that become hot and start to rise it temperature through conduction process. The heated water will then become less dense than the colder water that located above (unheated water). If there is any opening formed directly from the source of heat towards the surface such as fault, the heated water would be ejected easily and become springs.